Creative industries: a case study of Isfahan, Iran. Issue 2 (19th October 2018) - Ghazi, Elham Lafzi; Goede, Miguel
Abstract : Purpose: The purpose of this paper is to contribute critically to understanding the structure of creative industries in Isfahan. Design/methodology/approach: The authors first gather needed information about the case study and then analyze the data according to three measures of gross value added, employment and the dynamics of business for each sector of creative industries. Findings: Results indicate that creative industries are medium-sized domestic enterprises which are comparatively weak in productivity in some sectors. Originality/value: This paper illustrates the model of creative industries assessment for Isfahan city and, finally, provides a good understanding of the concept of the creative industries as a key element of the creative city.